The Sky Pilot in No Man's Land - Connor, Ralph, 1860-1937 (Salt Lake City, UT : Project Gutenberg, 2006)
"The Sky Pilot in No Man's Land" by Ralph Connor is a novel written in the early 20th century, likely during the First World War era. The story revolves around Barry Dunbar, a young man on a journey of self-discovery and faith as he grapples with his role as a missionary amid the backdrop of a drastically changing world. The characters, particularly Barry and his father Richard, are portrayed with depth as they navigate their relationships and the challenges posed by their diverse interactions with various people, including an adventurous American family and the local community. The opening of the novel introduces us to a tense yet intriguing scene involving Barry, who impressively takes a diving leap from a rock into a river, catching the attention of both his father and a young woman nearby. This initial encounter establishes Barry's athleticism and charming nature, while also highlighting the budding relationship with Paula, the daughter of an American oil explorer. The chapter smoothly transitions between their interactions, giving insight into Barry's character as a missionary and suggesting themes of adventure, friendship, and the struggle between societal expectations and personal aspirations. Overall, the opening sets the stage for an exploration of faith, identity, and moral choices against the backdrop of a world at war. (This is an automatically generated summary.)
Release date is 2006-06-03
Donald Lainson and David Widger
Keywords: World War, 1914-1918 -- Fiction